Effect of Different Levels of Nitrogen and Foliar Spray of DAP on Toria Grown as Utera Crop in Rice-Toria Cropping System - Duary, B.; Ghosh, A. K. (International Journal of Bio-resource and Stress Management, 2023)
An experiment was conducted to study the effect of different levels of nitrogen and foliar spray of 2 % DAP at Pre-flowering stage on toria, grown as utera crop during 2003-2004 in rice-toria cropping system in the lateritic belt of West Bengal. The treatments were control (No fertiliser), 20 kg N ha-1, 40 kg N ha-1, 60 kg N ha-1 and 80 kg N ha-1 alone and in combination with foliar spray of 2% DAP at Pre-flowering stage. The experiment was laid out in a randomized block design with three replications. Plant height at 60 DAS and at maturity and dry matter production at 60 DAS increased with increasing level of N up to 80 kg ha-1. Application of 80 kg N ha-1 though produced higher plant height at 60 DAS and at maturity, dry weight of plants at 60 DAS but 40 kg N ha-1 in combination with foliar spray of 2% DAP at Pre-flowering stage produced the highest number of seeds siliqua-1 (16.1), seed yield (364 kg ha-1), gross return (` 7470 ha-1), net return (` 3532 ha-1) and benefit:cost ratio (0.9). Though, seed yield increased significantly with increasing level of nitrogen up to 40 kg N ha-1, further increase in nitrogen level above 40 kg resulted in reduction in seed yield of toria.